KINERJA PENILAIAN INDIVIDU MENGGUNAKAN ANALISIS KATEGORI YANG TEPAT DALAM PROSES PEMILIHAN KARYAWAN - Widi, Angga; N, Eko Wahyu; Syukro, Ahedi (Jurnal Ilmu Manajemen Advantage, 2018)
For employers the process of employee selection is an important activity in the effort to get a workforce or adequate workers in receiving assignments to perform certain types of work. Many methods can be used in the employee selection process, one such method is category analysis. Whatever type of selection method, of course the company expects to achieve an accurate selection results. In writing this article the researcher wants to show one form of application of the method so that the selection result can give a picture of transparent result. This method is numerical using a score approach through a focus group discussion process. This categorical method is no less accurate than other similar methods in the recruitment selection process of employees in the company because it is quite objective.